2003
DOI: 10.1002/humu.9195
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a frequent variant inALG6, the cause of Congenital Disorder of Glycosylation-Ic

Abstract: Congenital Disorder of Glycosylation (CDG) type Ic is caused by mutations in ALG6.This gene encodes an α1,3 glucosyltransferase used for synthesis of the lipid linked oligosaccharide (LLO) precursor of the protein N -glycosylation pathway. CDG-Ic patients have moderate to severe psychomotor retardation, seizures, hypotonia, strabismus, and feeding difficulties. We previously identified a t ypical patient with a heterozygous point mutation, c.391T>C (p.Tyr131His) in ALG6. Using complementation analysis of ALG6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…LLO (lipid-linked oligosaccharides) analysis of fibroblasts shows an accumulation of Man9GlcNAc2 (Imbach et al 1999;Burda et al 1998;Marklova and Albahri 2007). A few isolated CDG-ALG6 patients (e.g., patients with the homozygous c.391TT>C, p.Y131H mutation) presented with a normal transferrin and LLO profile (Westphal et al 2003;Miller et al 2011). The Laboratory for Inborn Errors of Metabolism started screening for CDG in 1998 and Du Plessis et al (2001) reported on the first South African CDG patient.…”
Section: Introductionmentioning
confidence: 99%
“…LLO (lipid-linked oligosaccharides) analysis of fibroblasts shows an accumulation of Man9GlcNAc2 (Imbach et al 1999;Burda et al 1998;Marklova and Albahri 2007). A few isolated CDG-ALG6 patients (e.g., patients with the homozygous c.391TT>C, p.Y131H mutation) presented with a normal transferrin and LLO profile (Westphal et al 2003;Miller et al 2011). The Laboratory for Inborn Errors of Metabolism started screening for CDG in 1998 and Du Plessis et al (2001) reported on the first South African CDG patient.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] The frequency and the prevalence of the disease are not known. The diagnosis has to be confirmed by mutation analysis of ALG6.…”
Section: Analytical Validationmentioning
confidence: 99%
“…However, recent case of 11-year old Saudi Arabian boy with dilated cardiomyopathy which revealed a novel c.482A>G (p.Y161C) mutation, suggests that CDG should be considered in the diff erential diagnosis of unexplained cardiomyopathy (30). Two point mutations c.391T>C in exon 5 and c.911T>C in exon 10 resulting in p.Y131H and p. F304S, respectively, although assumed being single nucleotide polymorphisms (rs35383149 and rs17856039) (31,32) are particularly interesting. It was shown that p.F304S polymorphism may exacerbate the clinical outcome of other CDGs, especially in severely aff ected patients (33).…”
Section: Alg6-cdg (Cdg-ic)mentioning
confidence: 99%
“…It was shown that p.F304S polymorphism may exacerbate the clinical outcome of other CDGs, especially in severely aff ected patients (33). For the p. Y131H substitution it is still unclear whether the homozygous form c.391C/C is suffi cient to cause the disease or some additional genetic alteration has to be present (31). We have recently shown that the frequency of heterozygotes in Croatian population is 3 times higher (6.7%) than in US population (2.1%), the only one screened for p.Y131H until now (31,34).…”
Section: Alg6-cdg (Cdg-ic)mentioning
confidence: 99%
See 1 more Smart Citation